(untitled) (Editora Impacto Científico, 2026)
This article analyzes the historical development of History teaching in Brazil, focusing on the processes of construction and reconstruction of its disciplinary code over the centuries. From a theoretical-critical perspective, it discusses the curricular transformations, educational reforms, and ideological disputes that have shaped the discipline from the colonial period to the implementation of the National Common Curricular Base (BNCC). The study examines the role of official guidelines, school culture, textbooks, and public policies in defining teaching content and methods, highlighting continuities and disruptions that have influenced pedagogical practices. The article emphasizes the importance of adopting a plural, critical, and inclusive approach that acknowledges Brazil’s cultural diversity and fosters active citizenship. By problematizing the tensions between tradition and innovation, the work contributes to the ongoing debate on the direction of history education in the country, pointing to the challenges and possibilities of building a more reflective and democratic pedagogical practice. DOI: https://doi.org/10.56238/edimpacto2025.090-092